ELISITASI FOTO JURNALISTIK JENAZAH COVID-19 - Renate Pinasthika Handono; Taufan Wijaya (Specta: Journal of Photography, Arts, and Media, 2023)
Selama pandemi Covid-19 media massa memiliki peran memberikan informasi terbaru kepada masyarakat, termasuk dalam bentuk foto. Dengan demikian, kehadiran foto jurnalistik penting bagi khalayak untuk memperoleh gambaran peristiwa pandemi global. Salah satu foto jurnalistik yang menampilkan jenazah pasien sempat menjadi kontroversial pada pertengahan Juli 2020. Berangkat dari foto tersebut, peneliti berusaha melihat bagaimana jurnalis foto memaknai etika foto jenazah Covid-19. Penelitian ini menggunakan teknik wawancara elisitasi foto atau Photo Elicitation Interview (PEI). Teknik wawancara ini melibatkan foto yang dibawa dari peneliti kepada narasumber. Peneliti mewawancarai lima jurnalis foto di Indonesia yang aktif melakukan liputan pandemi. Temuan penelitian ini menunjukkan pandangan jurnalis foto terhadap foto jenazah Covid-19 yang ditayangkan dan dipilih oleh peneliti memenuhi kode etik jurnalistik, meskipun pada masa sebelum pandemi foto jenazah dianggap tabu untuk terbit di media.Elicitation of Photojournalism on the Body of a Suspected Covid-19. During the Covid-19 pandemic, the mass media had a role in providing the latest information to the public, including in the form of photography. Then photojournalism is essential for the audience to get an overview of the global pandemic events. One of the journalistic photos showing the patient's corpse became controversial in mid-July 2020. Starting from this photo, the researchers tried to see how photojournalists interpret the ethics of taking photos of Covid-19 corpses. This study uses a Photo Elicitation Interview (PEI) technique. This interview technique involves taking photos from the researcher to the resource person. Researchers interviewed five photojournalists in Indonesia who were actively covering the pandemic. The findings of this study show that photojournalists' views on photos of Covid-19 corpses that were broadcast and selected by researchers met the journalists’ code of ethics, even though in the pre-pandemic period, photos of corpses were considered taboo to be published in the media.